Well-off but powerless? Status incongruence and psychological well-being in contemporary China. (August 2019) - Jin, Lei; Tam, Tony; Tao, Lin
Abstract: During recent decades, China has experienced rapid economic growth, but the authoritarian state has continued to hold tight control over the access to political power. Scholars have long suspected that the incongruence between growing economic resources and lack of political power may spawn dissatisfaction and anxiety. But little empirical research has systematically assessed the incongruence and its psychological consequences in China. Moreover, social theorists have disagreed on the consequences of status incongruence and empirical examination has been inconclusive so far. Therefore, we ask: 1) do Chinese people perceive the incongruence between their economic conditions and access to power? And 2) does this incongruence affect their psychological well-being? We applied the diagonal mobility model from stratification research to analyze data from a nationally representative survey in China so as to assess the incongruence between power and wealth status and adjudicate its consequences. We found that Chinese people perceived substantial gaps in their power and wealth status. Contrary to what theorists of status inconsistency expect, the incongruence between power and wealth status does not harm psychological well-being. Consistent with the prediction of the synthesizing approach, individuals tend to emphasize the status dimension in which they enjoy advantages and discount the dimension in which they suffer detriments. Adding to the literature on the social determinants of health, this study shows how the multi-dimensional nature of social stratification affect the disparities of psychological well-being in contemporary China. Highlights: Chinese people in general placed themselves at the bottom of power hierarchy. They perceived substantial gaps between power and wealth status. The incongruence between power and wealth status does not affect psychological well-being. Power and wealth status compensate each other in their effects on psychological well-being.